Association of metformin use with risk and survival outcome of esophageal cancer in patients with diabetes: A systematic review and meta-analysis - Hui Xie; Muhan Li; Zhaoqi Chen; Yuling Zheng (PLoS ONE, 2025)
The purpose of this study was to conduct a systematic review and meta-analysis to investigate the association between the utilization of metformin and the occurrence and survival rate of esophageal cancer (EC) in individuals with diabetes. Methods: A systematic review and a meta-analysis were performed. Related literature was searched from databases, including PubMed, Embase, Web of Science, and Cochrane Library, covering the period from the inception of these databases until July 2023. Results: A total of 16 studies were eligible, including twelve reporting incidences of EC and four reporting OS of EC patients. The combined findings revealed a significant association between the use of metformin and a lower risk of EC (OR, 0.87, P = 0.04). Furthermore, metformin could significantly prolong the OS time (HR, 0.87, P = 0.002). In analyses stratified by treatment modalities, metformin combined with surgery and neoadjuvant chemoradiotherapy presented the strongest protective effect on EC patients with diabetes (HR, 0.38, P = 0.003). Conclusion: Our meta-analysis indicated that the use of metformin might reduce the EC incidence and improve the OS in EC patients with diabetes.